Exploration of Mathematics Learning Motivation of Madrasah Aliyah (MA) Students in Geometry Material - Rahmad Sugianto; Akhsanul In'am; Niswatun Hasanah; Annisa Nurina Vidyastuti; Muhammad Ruskhan Fauza (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
In this study, the researcher made preliminary observations on students of class XI IPA at MAN 2 Malang City, there were still students who had low learning motivation in participating in mathematics. It can be seen from the mid-semester learning outcomes, namely around 37% of student learning outcomes under the minimum completeness criteria (KKM). The purpose of this study was to explore students' motivation in mathematics in geometry material. The research was conducted at MAN Malang City. The population in this study were all students of class XI MIPA at MAN 2 Malang City, totaling 226 students consisting of 8 classes. Sampling was done by simple random sampling, the number of samples was 150 students. The instrument used was the questionnaire method, the measurement scale used in this questionnaire instrument was a Likert scale with a checklist form (√). Based on this research data, it was found that the objective indicator of intrinsic orientation obtained a score of 3.68% in the good category. Meanwhile, indicators of extrinsic motivation are categorized as good with a percentage of 3.72%. The task score indicator is categorized as good with a score of 3.80%. Trust control indicators for learning to get 3.50% are categorized as good. The self-confidence indicator with a score of 3.57% indicates good criteria. The last indicator of anxiety when the test scores 3.32% indicates good criteria. By having high learning motivation, students will be able to overcome their anxiety when approaching exams as a challenge that must be faced to achieve success